Arsitektur Kolonial di Heerenstraat dalam Upaya Pelestarian Warisan Budaya Kota Probolinggo, Jawa Timur - Melisa Anggraeni, Susi; Srijaya, I Wayan; ., Kristiawan (Humanis; Vol 24 No 2 (2020)DO - 10.24843/JH.2020.v24.i02.p12, 2020)
Probolinggo is the one of cities in East Java that has many cultural heritages, especially in colonial architectural. There are many colonial architectural heritages in Probolinggo, especially in the center of city Heerenstraat area (Jalan Suroyo). This study aimed to determine the style, past and present functions, and the efforts in preserving colonial architectural in Heerenstraat Probolinggo. There are five places were used as objects of study, they are basecamp of Kodim 0820, Museum of Probolinggo, GPIB "Immanuel Church", Alun-alun or city center, and Probolinggo Train Station. Nowadays, each of these objects is still functioning and has a unique arsitectural style that representing the developed architectural in Probolinggo. This study used architectural, functional, and conservation theories. Furthermore, the stylistic, contextual, and architectural analysis method were applied in this study. The results of this study are knowing about the architectural style, the functions from the past and present of each research object, and the efforts in preserving colonial architectural that have been done and need to be done.